Synthesis, Characterization, and Handling of EuII-Containing Complexes for Molecular Imaging Applications - Basal, Lina A.; Allen, Matthew J. (Frontiers in Chemistry, 2018)
Considerable research effort has focused on the in vivo use of responsive imaging probes that change imaging properties upon reacting with oxygen because hypoxia is relevant to diagnosing, treating, and monitoring diseases. One promising class of compounds for oxygen-responsive imaging is EuII-containing complexes because the EuII/III redox couple enables imaging with multiple modalities including magnetic resonance and photoacoustic imaging. The use of EuII requires care in handling to avoid unintended oxidation during synthesis and characterization. This review describes recent advances in the field of imaging agents based on discrete EuII-containing complexes with specific focus on the synthesis, characterization, and handling of aqueous EuII-containing complexes.